Sociological and Marxist Analysis of Surveillance in the Process Leading to Data Surveillance - Eyüp Al (Türkiye İletişim Araştırmaları Dergisi)
The aim of this study is to expose data surveillance to sociological and Marxist analysis by revealing different stages of surveillance from past to present. Social outcomes of surveillance with sociological analysis, economic and political reasons of surveillance with Marxist analysis are discussed. However, it is claimed that the modern structure of surveillance has been opened to discussion, and its digitalization and fluidization have given birth to data surveillance as a new surveillance and control form. Therefore, the classical surveillance conditions defined around Bentham’s idea of “Panopticon” and Foucault’s texts have changed a lot. Since this change is not only structural, the stages of the surveillance mechanism and its aims in the historical process are open to discussion. In the contemporary period, surveillance has also transformed at a point where speed and flexibility determine all kinds of everyday actions. In order to understand this transformation, this article examines how surveillance reaches a more fluid and mobile form, and the actions performed in digital environments are followed on the data axis instead of tracking the body. As a result, it is concluded that the forms of surveillance move away from oppression, individuals are included in surveillance voluntarily, data surveillance is used for economic and political interests, and data provides much more efficient, individual and instant information without any time and place limits.